Education, Growth and Income Inequality - Thijs van Rens (Center for Economic Studies and ifo Institute (CESifo), 2002)
When types of workers are imperfect substitutes, the Mincerian rate of return to human capital is negatively related to the supply of human capital. We work out a simple model for the joint evolution of output and wage dispersion. We estimate this model using cross-country panel data on GDP and Gini coefficients. The results are broadly consistent with our hypothesis of diminishing returns to education. The implied elasticity of substitution fits Katz and Murphy's (1992) estimate. A one year increase in the stock of human capital reduces the rate of return by about 2 per cent. The combination of imperfect substitution and skill biased technological change closes the gap between the Mincer equation and GDP growth regressions almost completely.
Keywords: 330